Disguised unemployment in under - developed countries - Ghosh, B. N. (New Delhi, 1977)
The lack of understanding of the economics of agriculture in low income countries stems in large part from the confusion caused by widely held doctrines about the agricultural sector. It is obvious that a lack of economic knowledge breeds doc trines that become entrenched dogmas. These doctrines have led to false answers to the question: What is the role of agri culture in economic growth? The doctrinal answers that have plagued low income countries run as follows: the opportunity for growth from agricultural production is the least attractive source; agriculture can provide much of the capital required to mount industrialization; it also can provide an unlimited supply of labor for industry; it can even provide much labor at zero opportunity costs given the doctrine that a considerable part of the labor force in agriculture is redundant in the sense that its marginal productivity is zero.
Keywords: Disguised unemployment